Anaesthesiology & Critical Care Postgraduate Training in Malaysia : training curriculum - Md Hashim, Noorjahan Haneem; Md Ralib, Azrina; Chan, Yoo Kuen; Foo, Li Lian; Shariffuddin, Ina Ismiarti; Md Zain, Jaafar; Abdul Mukmin, Laila; Lee, Choon Yee; Mansor, Marzida; Mohd Mansor, Melor@Mohd Yusof; Zakariah, Mohd Fahmi; Nik Mohamad, Nik Abdullah; et al. (Majlis Dekan Fakulti Perubatan Universiti Awam Malaysia, UM, 2023)
This document is the National Postgraduate Medical Curriculum (NPMC) for Anaesthesiology and Critical Care, and is part of the NPMC Project which is intended to cover the development of curricula for all clinical medical specialists in Malaysia. It is to ensure that the training is consistent and competency based, and meets the standards required by the respective national bodies and the National Specialist Register (NSR).